Government Crisis Communication Strategies in Dealing with Misinformation in the Digital Era - Amina, Nurtyasih Wibawanti Ratna; Satriya, Bambang; Sadhana, Kridawati; Sadono, Teguh Priyo (Journal of Dialogos, 2025)
This research aims to understand in depth the crisis communication strategies implemented by the government in dealing with misinformation in the digital era. The rapid spread of misinformation in the digital space is a serious challenge, especially in crisis situations that demand fast, accurate, and reliable communication responses. This research uses a qualitative approach with a descriptive method, focusing on government institutions that have a strategic role in public communication, such as the Ministry of Communication and Information Technology (Kominfo) and the National Disaster Management Agency (BNPB). Data was collected through in-depth interviews with key informants, documentation studies, digital media observations, and analyzed using qualitative content analysis through the stages of data reduction, data presentation, and conclusion drawn. The results show that although the government has utilized social media as the main channel in crisis communication, challenges such as limited message reach, lack of coordination between agencies, and low public trust still hinder the effectiveness of the strategy. Cross-sectoral cooperation, people's digital literacy, and the role of credible and trained spokespeople are key factors in building information resilience and increasing public trust during crises. Therefore, an adaptive, transparent, and data-based crisis communication strategy is indispensable to maintain social stability in the midst of dynamic digital information flows